Community Perceptions Of The Existence Of Poultry Slaughterhouses In Baruga District, Kendari City - Awal Maulid Sari; Inal Inal; Hajar Hajar (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2025)
This study aims to identify community perceptions of the existence of poultry slaughterhouses (RPA) in Baruga District, Kendari City. The presence of RPAs often generates both support and opposition among residents, particularly regarding environmental cleanliness, comfort, health, and local economic aspects. This research employed a qualitative descriptive approach using survey methods through questionnaires and in-depth interviews with 40 respondents living around the RPA area. The findings indicate that most residents hold negative perceptions toward the existence of RPAs due to unpleasant odors, wastewater that disrupts drainage systems, and noise from slaughtering activities that disturb comfort. However, some residents view the RPA as beneficial for providing employment opportunities and ensuring access to fresh chicken meat. The main factors influencing public perception are inadequate waste management and the close proximity between residential areas and RPA locations. Therefore, it is necessary to improve the management of RPAs, particularly in sanitation and waste treatment aspects, so that their presence can be sustainably accepted by the surrounding community.